Stigma-making and narrative ethics in Singaporean cultural representations of HIV and AIDS - Hyder, Sophia (Nanyang Technological University, 2023)
Since the start of the AIDS epidemic in the 1980s, significant medical strides have improved the quality of life and life expectancy for people living with HIV. Nevertheless, cultural perceptions of HIV and the people living with them have not advanced at the same pace. In Singapore, discrimination continues to occur against people with HIV across various aspects of life, such as employment, healthcare, and interpersonal relationships, impeding their access to treatment and social support. This thesis examines the diverse HIV and AIDS narratives in Singapore and traces the developments of deeply-rooted stigmas within the cultural imaginary. By scrutinising the construction, deconstruction, interpretation, and reception of the diverse HIV and AIDS narratives in Singapore, this study unveils the developments of deeply-rooted stigmas within the local cultural imaginary. The thesis aims to: (i) trace the creation, reinforcement, and evolution of cultural imaginaries related to HIV, AIDS, and the people living with them; (ii) scrutinise documentary, collaborative, and authorial processes of stigma- (un)making in mass media, literature, and theatre; and (iii) problematise pervasive and persistent ways of looking at people living with HIV or AIDS. The first chapter uncovers the origins of Singaporean stigma, tracing it to western notions of decadence and deviance. The second chapter delves into narrative power, analysing the complexities faced by storytellers and subjects, and emphasises the need for counter-images of HIV and AIDS. The final chapter expounds on anonymity’s role and reveals its potential to perpetuate stigma rather than alleviate it, urging a nuanced approach to visibility and perception. Collectively, the thesis dismantles deeply ingrained misconceptions about HIV and AIDS in Singapore, emphasising the significance of these narratives in shaping lived experiences. In the context of a shifting healthcare landscape and community-based care, this thesis highlights the vital role of narratives in influencing attitudes and behaviors. Through the exploration of the creation, dismantling, and ethical considerations of stigmatic narratives, the study unveils the delicate balance between stigma’s endurance and vulnerability. For a condition as deeply embedded in cultural contexts as HIV and AIDS, analysing the trajectory and mechanisms of narratives offers insights into the persistence of these narratives and strategies to counteract them.